Production of CO2 in crude oil bioremediation in clay soil - Baptista,Sandro José (2005)
The aim of the present work was to evaluate the biodegradation of petroleum hydrocarbons in clay soil a 45-days experiment. The experiment was conducted using an aerobic fixed bed reactor, containing 300g of contaminated soil at room temperature with an air rate of 6 L/h. The growth medium was supplemented with 2.5% (w/w) (NH4)2SO4 and 0.035% (w/w) KH2PO4. Biodegradation of the crude oil in the contaminated clay soil was monitored by measuring CO2 production and removal of organic matter (OM), oil and grease (OandG), and total petroleum hydrocarbons (TPH), measured before and after the 45-days experiment, together with total heterotrophic and hydrocarbon-degrading bacterial count. The best removals of OM (50%), OandG (37%) and TPH (45%) were obtained in the bioreactors in which the highest CO2 production was achieved.